Hill-Climbing Search (HCS) mppt algorithm for hydrokinetic energy harnessing - Nasiruddin, Sadan; Wan Ismail, Ibrahim (Institution of Engineering and Technology, 2022)
Hydrokinetic turbines based on rivers are environmentally friendly technology that has increased interest in advanced scientific research during the last decade. The kinetic energy formed from the water stream can be harnessed as long as the water is flowing. Nevertheless, the variation and fluctuation of water current speed and turbulence flow in a river is the main issue, especially in designing a control system that can harness the maximum output with high efficiency. Various methods and techniques have been applied in hydrokinetic energy conversion systems to extract maximum power. This paper presents the performance of the Hill Climbing Search (HCS) MPPT Algorithm in hydrokinetic energy harnessing in terms of steady-state oscillation, time tracking, and efficiency. The model of hydrokinetic energy harnessing is developed using MATLAB/Simulink that comprises a water turbine, permanent magnet synchronous generator (PMSG), passive rectifier, and DC boost converter. The MPPT algorithm can be employed in the DC boost converter by regulating the ratio of the duty cycle. The results show the HCS MPPT algorithm reduced the steady-state oscillation, rapid time tracking and improved 93.75% of efficiency.